Analisis Kinerja Keuangan Pemerintahan Dinas Lingkungan Hidup Berdasarkan Anggaran - Harahap, Anggi Safriani; Lubis , Arnida Wahyuni (Balance : Jurnal Akuntansi dan Manajemen, 2022)
This study aims into analyzing the financial performance of Local Governments it the environmental Service of import Sumatera Utara. A case study of employee operational expenditures by using independent ratio analysis. effectiveness ratio of Local revenue, efficiency ratio, and harmony ratio. based on the financial report of the government of the environment Office analysis techniques. the result of this study indicates that the financial performance of the North Sumatra environmental Service Government its into optimal.